E6 and E7 Gene Polymorphisms in Human Papillomavirus Types-58 and 33 Identified in Southwest China - Chen, Zuyi; Jing, Yaling; Wen, Qiang; Ding, Xianping; Wang, Tao; Mu, Xuemei; Chenzhang, Yuwei; Cao, Man (PloS one, 2017)
Cancer of the cervix is associated with infection by certain types of human papillomavirus (HPV). The gene variants differ in immune responses and oncogenic potential. The E6 and E7 proteins encoded by high-risk HPV play a key role in cellular transformation. HPV-33 and HPV-58 types are highly prevalent among Chinese women. To study the gene intratypic variations, polymorphisms and positive selections of HPV-33 and HPV-58 E6/E7 in southwest China, HPV-33 (E6, E7: n = 216) and HPV-58 (E6, E7: n = 405) E6 and E7 genes were sequenced and compared to others submitted to GenBank. Phylogenetic trees were constructed by Maximum-likelihood and the Kimura 2-parameters methods by MEGA 6 (Molecular Evolutionary Genetics Analysis version 6.0). The diversity of secondary structure was analyzed by PSIPred software. The selection pressures acting on the E6/E7 genes were estimated by PAML 4.8 (Phylogenetic Analyses by Maximun Likelihood version4.8) software. The positive sites of HPV-33 and HPV-58 E6/E7 were contrasted by ClustalX 2.1. Among 216 HPV-33 E6 sequences, 8 single nucleotide mutations were observed with 6/8 non-synonymous and 2/8 synonymous mutations. The 216 HPV-33 E7 sequences showed 3 single nucleotide mutations that were non-synonymous. The 405 HPV-58 E6 sequences revealed 8 single nucleotide mutations with 4/8 non-synonymous and 4/8 synonymous mutations. Among 405 HPV-58 E7 sequences, 13 single nucleotide mutations were observed with 10/13 non-synonymous mutations and 3/13 synonymous mutations. The selective pressure analysis showed that all HPV-33 and 4/6 HPV-58 E6/E7 major non-synonymous mutations were sites of positive selection. All variations were observed in sites belonging to major histocompatibility complex and/or B-cell predicted epitopes. K93N and R145 (I/N) were observed in both HPV-33 and HPV-58 E6.